A 25-year long monitoring of lead content in the blood of cows from a stationary polluted area. (8th November 2007) - Zadnik, Tomaz
The monitoring has been performed on lead content in the blood of cows (n = 1, 279) from farms (n = 1?14) near a former lead mine and current smelting plant from 1975 to 2003. Early measurements showed that average lead concentration in the blood of cows was 1.25 ? 0.58 mg/kg while in 2002 it was about 10-times to 20-times lower (0.069 ? 0.005 mg/kg). Significant decrease in blood lead concentration is attributed to the sanitation of the major source of industrial emission of lead gases and dust by installation of bag filters to the plant chimneys in 1978.